PEMBUATAN MINUMAN SARI BIJI DURIAN (Durio Zibethinus) DENGAN PENAMBAHAN EKSTRAK JAHE MERAH (Zingiber officinale rosc.) - Alhim, Rusdi; Wijaya, Mohammad; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aims to determine the effect of concentration of ginger on the quality ofÂ  juice of seeds durian and The level of panelist acceptance.Â  Parameters observed in this study included organoleptic test (aroma, taste, and color) and proximate test (protein and fat). The data analysis used is variance analysis. The results showed that the best organoleptic test results were found in the treatment with the addition of 94% juice of seeds durian with the addition of 6% red ginger extract. While the best proximate test results were found in the treatment with the addition of 100% juice of seeds durian with the addition of red ginger extract of 6%.